Nanotechnology for Lithium-Ion Batteries - Abu-Lebdeh, Yaser; Davidson, Isobel; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2013)
Nanotechnology and lithium-ion battery technology will both play a major role in helping the world solve its growing energy and environmental challenges. Nanotechnology for Lithium-Ion Batteries explores where the two fields converge, with fresh insights into the complex relationship between these rapidly growing areas of research. This book covers the basic concepts of nanotechnology, how they relate to lithium-ion batteries, and the effects of using nanomaterials to enhance battery performance. In addition to taking an in-depth look at the emerging research, this book will explore how new discoveries will impact existing and emerging markets, including those related to consumer electronics, automotive technology, and smart grid technology.
Introduction -- Inverse opal nanoarchitectures as Lithium-ion battery materials -- Nano-engineered silicon anodes for Lithium-ion rechargeable batteries -- Tin-based anode materials for Li-ion batteries -- Beyond intercalation: Nanoscaled enabled conversion anode materials for Li-ion batteries -- Graphene-based composite anodes for Lithium-ion batteries -- Nano-sized and nano-structured cathode materials for Li-ion batteries -- Design and properties of LiFePO4 nano-materials for high power applications -- Effect of nanoparticles on electrolytes and electrode/electrolyte interface -- Micro scaled three dimensional architectures for battery applications.
Keywords: Nanochemistry; Electrochemistry; Energy systems; Nanochemistry; Electrochemistry; Energy Systems